Selective Schooling Has Not Promoted Social Mobility in England - Franz Buscha; Emma Gorman; Patrick Sturgis (Institute of Labor Economics (IZA), 2021)
In this paper we use linked census data to assess whether an academically selective schooling system promotes social mobility, using England as a case study. Over a period of two decades, the share of pupils in academically selective schools in England declined sharply and differentially by area. Using a sample of census records matched to administrative data on selective system schooling within local areas, we exploit temporal and geographic variation to estimate the effects of the selective schooling system on absolute and relative social class mobility. Our results provide no support for the contention that the selective schooling system increased social mobility in England, whether considered in absolute or relative terms. The findings are precisely estimated and robust to a comprehensive battery of robustness checks.
Keywords: I21; 124; 128; J18; J24; 330; social mobility; selective schooling; grammar schools